2019
DOI: 10.1111/scs.12736
|View full text |Cite
|
Sign up to set email alerts
|

eHealth tool for patients with abdominal aortic aneurysm: development and initial evaluation

Abstract: Rationale Abdominal aortic aneurysm (AAA) is a prevalent condition among elderly men and may require surgical repair. Recent technical advances offer new opportunities to provide patients and next of kin with tailored and individualised information. eHealth tools have proven useful in other patient cohorts, but there are currently no validated educational eHealth tools for patients with AAA. Aim Our aim was to develop and evaluate an eHealth tool for patients with abdominal aortic aneurysm using a participator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The first step was to explore the learning needs of patients regarding their AAA and the care trajectory 8 . The second step entailed the development and validation of the eHealth tool in collaboration with patients and healthcare staff, aiming to enhance the usability and relevance of the tool 13 . The present study presents the final step of development, where the eHealth tool was tested and implemented in a real-life setting with patients planned for surgical treatment of AAA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first step was to explore the learning needs of patients regarding their AAA and the care trajectory 8 . The second step entailed the development and validation of the eHealth tool in collaboration with patients and healthcare staff, aiming to enhance the usability and relevance of the tool 13 . The present study presents the final step of development, where the eHealth tool was tested and implemented in a real-life setting with patients planned for surgical treatment of AAA.…”
Section: Methodsmentioning
confidence: 99%
“…The content of My aorta (version 1) was also made available as a print-out for those who preferred paper format instead of using the app. The eHealth tool aimed to provide structured and balanced information and consisted of six chapters regarding the condition, self-care and surgical treatment 13 . It was designed to enable self-directed navigation and did not include time triggers or forced entries.…”
Section: Methodsmentioning
confidence: 99%
“…Digital health technology has brought new tools to share medical knowledge, with a growing interest in applications to empower patients and provide them with appropriate information and education on their disease [ 51 , 52 ]. With that aim, some authors developed an educational e-health tool for patients with AAA and assessed its content and usability through questionnaires and focus group interviews [ 53 ]. Healthcare professionals’ feedback indicated that the content corresponded to the information that they usually provide to patients.…”
Section: Telemedicine and Aortic Diseasementioning
confidence: 99%
“…Healthcare professionals’ feedback indicated that the content corresponded to the information that they usually provide to patients. Users’ feedback showed that the understandability and content was adequate, suggesting that the tool could improve communication and access to information in these patients [ 53 ]. They further investigated the interest in this application to reduce anxiety in patients with AAA undergoing surgery [ 54 ].…”
Section: Telemedicine and Aortic Diseasementioning
confidence: 99%